Optimizing anti-thymocyte globulin dosing in allogeneic hematopoietic stem cell transplantation: individualized approaches and clinical implications - Wang, Haitao; Yang, Hongqi; Du, Jishan; Dou, Liping; Liu, Daihong (Frontiers in Immunology, 2025)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative therapy for hematologic malignancies. However, the initial clinical experience with allo-HSCT revealed a concerning prevalence of severe graft-versus-host disease (GVHD) and graft failure. Subsequent randomized studies highlighted the role of anti-thymocyte globulin (ATG) in reducing acute and chronic GVHD and graft failure, although it did not improve overall survival. Pharmacodynamic studies have established an association between ATG concentration and the incidence of GVHD and life-threatening infections. However, ATG concentration at designated timepoints showed no such correlations with non-relapse mortality and overall survival in allo-HSCT. There is a delicate balance between ATG exposure and the outcomes of allo-HSCT. More specifically, insufficient ATG exposure may diminish its function on GVHD prophylaxis, while excessive ATG may delay immune reconstitution and increase risk of disease relapse and infection. Considering the significant inter-individual heterogeneity in ATG pharmacokinetics, individualized ATG dosing could potentially increase the proportion of transplant recipients attaining the optimal ATG exposure. Recent studies have shown that individualized ATG dosing, guided by absolute lymphocyte count or therapeutic drug monitoring, can improve optimal exposure attainment rate. Which indicated a potential approach to achieve superior transplant outcomes. This review summarizes the advances and the challenges of individualized ATG dosing in allo-HSCT.